Felix Mitterer's Besuchszeit and Sibirien: Humanizing the Socially Critical Volksstück - Gerhard, Christine (My University, 1997)
Felix Mitterer is a well-known Austrian playwright who has yet to receive extensive recognition in North America. He writes in the tradition of the Volksstück, a genre which is usually associated with clichés, crude comedy, sentimentality and entertainment for the masses. But increasingly, authors have manipulated the traditional aspects of this genre to create Volksstücke with a socially critical message. Mitterer has been associated with a movement begun in the late sixties known as the "new socially critical Volksstück." Most writers of this movement address provocative themes, but have alienated the intended audience of the Volksstück, the ordinary people, by creating works which are cynical, surreal or violent. Mitterer has modified the socially critical Volksstück so that it appeals to a wide audience.
I will analyze how Mitterer has accomplished this by examining his two most popular and widely performed plays, Besuchszeit and Sibirien. I will explore his presentation of provocative themes - alienation resulting from a lack of communication, the problematic nature of traditional gender roles, difficulties arising from unrestrained progress, and the dehumanizing nature of institutions - and his manipulation of traditional Volksstück elements in order to demonstrate his unique combination of the mundane and the artistic. Then I will examine the critical response to performances of these two works in Austria, Germany and Switzerland, focusing on newspaper reviews, the major source of information on his works, in order to understand the strengths and weaknesses of his method of presentation. I will conclude by showing how he has modified both the traditional and the new socially critical Volksstück to create a more human version of this which appeals to a wide audience while achieving critical and scholarly recognition.
Keywords: German; German Language and Literature; German Language and Literature